NGHIÊN CỨU LỰA CHỌN HƯƠNG LIỆU VÀ XÂY DỰNG QUY TRÌNH CÔNG NGHỆ SẢN XUẤT CHÈ ĐEN ƯỚP HƯƠNG HOA QUẢ ĐÓNG TÚI LỌC - Chương, Đỗ Văn (Vietnam Journal of Science and Technology, 2012)
SUMMARY PRODUCTS OF FRUIT FLAVORED TEA IN FILTERED BAGS Products of fruit flavored tea in filtered bags are researched and produced from CTC black tea, which are produced with high quality of Tam Duong-Lai Chau tea company. Then they are blended with other chosen fruit flavor of Republic of France at a rate of 1.6% (16 ml of oil / 1 kg of tea) for mango flavor, strawberry flavor, peach flavor and at a rate of 1.2% (12 ml of oil / 1 kg of tea) for apricot flavor. Appropriately marinated time is 30 days for four kinds of scent to create products with high quality that is equivalent to SriLanKa’s Dilmah tea. These products, which contribute to diversify the tea products of Vietnamese tea sector and to meet the increasing demand for high quality, various types in the domestic and foreign market, make Vietnam's tea stand on a par with other countries's tea in the region and in the world. Keyword. Black tea, Tea in filtered bags, Flavored tea, essential oil.